Kompensasi, Organizational Climate dan Organizational Culture terhadap Employee Performance dengan Innovative Behavior sebagai Variabel Mediasi - Windi Windi (IPM2KPE, 2024)
This research aims to determine the influence of Compensation, Organizational Climate and Organizational Culture on Employee Performance with Innovative Behavior as a Mediating Variable.The method used is a quantitative descriptive method. The results of the research show that Innovative Behavior can positively and significantly mediate the influence of Compensation, Organizational Climate and Organizational Culture on Employee Performance. Keywords: Employee Performance, Innovative Behavior, Organizational Climate